Loan provision and investment banking in the function of the BIH economy - Starčević Vitomir; Jovičić Ankica; Zupur Ognjen (Ekonomski Pogledi, 2013)
Developed market economies and their banking systems, in recent decades, increasingly shaped by a new strategy of banking business. Banks are those that adapt to the radical changes and innovations in production, trade and the financial structure of the economy, or to changes in the financial markets. Very often banks that are pulling you, or initiate, their actions are directed processes of global economic restructuring and the banks conduct innovative activities in the area of new business strategies and policies to guide overall business. One way is to take the bank through our business practices are redirected to the issuance, sale and purchase and transfer of securities. On the other hand, it initiates a relatively declining importance of traditional deposit and loan banking. In developed market economies with developed financial markets and the extensive network of intermediary financial institutions, securities, and business for the banks they have a far greater importance than it is now in Bosnia and Herzegovina. Hence a portfolio of securities in the financial statements of the Bank significant. Commitment to this subject is in pointing to the future importance of that in Bosnia and Herzegovina securities had to have in the banking business.